The Degree of Influence of Daily Physical Activity on Quality of Life in Type 2 Diabetics - Zhang, Feng; Huang, Li; Peng, Li (Frontiers in Psychology, 2020)
Objectives：This study mainly explored the degree of influence of daily physical activity (PA) on the Quality of life (QoL), then provided a basis for improving PA and QoL in patients with Type 2 Diabetic Mellitus (T2DM). Methods：Respectively using Long International PA Questionnaire (IPAQ-L) and Diabetic Mellitus QoL Scale (DMQLS) to investigate the daily PA and QoL of patients with T2DM.. And the obtained data was analyzed by SPSS19.0 data analysis software. The correlation between PA and QoL was analyzed by pearson correlation analysis and the degree of influence of PA on the QoL of patients with T2DM was analyzed by optimal scale regression analysis. Results：The total daily PA of the participants was 1172.79 ± 1266.23 MET-min / w and the overall score of QoL was 149.17 ± 17.16 points. Positive correlation have been found between PA and QoL and its all dimensions（all P <0.05）. It was found in the optimal scale regression that among many influencing factors, PA was the significant and ranking the first in factors of the patient's total QoL (importance = 0.432, P<0.05) and its disease, physiological, psychological and social dimension. The degrees of influence of PA on sub-dimensions of QoL were in the order as physiology (0.476), society (0.441), disease (0.388), psychology (0.377), and satisfaction (0.089). Conclusions：The level of daily PA of patients with T2DM in southwest of China was moderate. Among the influencing factors as gender, age, course of disease, education background, monthly income, BMI, work status and complications, daily PA is the most important factor for QoL and its physiological, social, psychological and disease dimension. The degrees of influence of daily PA on sub-dimensions of QoL were in the descending order as physiology, social, disease, psychology, and satisfaction. Therefore, in view of the importance of daily PA for QoL, more attention should be paid to the daily PA of T2DM patients in the future, including the study on more targeted testing methods, promotion strategies of daily PA and its more extensive positive effects.